40 Years of Low‐Temperature Electrolytes for Rechargeable Lithium Batteries - Li, Zeheng; Yao, Yu‐Xing; Sun, Shuo; Jin, Cheng‐Bin; Yao, Nan; Yan, Chong; Zhang, Qiang (Angewandte Chemie International Edition, 2023)
Rechargeable lithium batteries are one of the most appropriate energy storage systems in our electrified society, as virtually all portable electronic devices and electric vehicles today rely on the chemical energy stored in them. However, sub‐zero Celsius operation, especially below −20 °C, remains a huge challenge for lithium batteries and greatly limits their application in extreme environments. Slow Li+ diffusion and charge transfer kinetics have been identified as two main origins of the poor performance of RLBs under low‐temperature conditions, both strongly associated with the liquid electrolyte that governs bulk and interfacial ion transport. In this review, we first analyze the low‐temperature kinetic behavior and failure mechanism of lithium batteries from an electrolyte standpoint. We next trace the history of low‐temperature electrolytes in the past 40 years (1983–2022), followed by a comprehensive summary of the research progress as well as introducing the state‐of‐the‐art characterization and computational methods for revealing their underlying mechanisms. Finally, we provide some perspectives on future research of low‐temperature electrolytes with particular emphasis on mechanism analysis and practical application. The 40 years development of low‐temperature electrolytes for rechargeable batteries has been reviewed. Critical insights are given from both underlying mechanistic and practical engineering aspects while we traverse the history on the rational design of low‐temperature electrolyte systems.